?INFLUENCE OF SOME ADDITIVES ON THE QUALITY OF COOKED, EMULSION· TYPE BEEF SAUSAGE AND CANNED PRODUCTS (Biological Sciences - PJSIR, 1995)
Cooked, emulsion-type sausage waspreparedfrom50%leanbeef,33%beef fattissuesand 17% ice.The effects of several additives on thecharacteristics of thecooked product wereexamined.The additives included 0.3% sodium diphosphate, 2%soy protein isolate (SPI)emulsion, 2%dry SPI, 2%sodiumcaseinate (SC)emulsion, 2%dry SC and 2% modified starch (MS). A portion of each batch was canned at 121°C for 90 min. Sodium diphosphate and starch enhanced the absorption of separated fluidsduring canning whencanned products werestored at 37°C for 7 days and no swelling or changes in the overall acceptability occurred during storage. Best treatment was the sodium diphos- phate which alsohadhighest organoleptic scoresandmarkedlyhighredcolourintensitywhensausages wereprepared with other additives. Sausages prepared with dry SPI and SC were acceptable and given higher organoleptic scores than those prepared with SPI and SC emulsions. The lowest organoleptic scores were given for the control sample. The present work was conducted to improve the binding ability, tenderness and texture of cooked, emulsion type sausage.The effect of somecommon sausagesandproductionof highqualitybeef sausages andcanned products were also studied.